Impact of weight indicators of TOPSIS technique in the selected district in the Slovak republic - Vavrek, Roman; Adamišin, Peter (Journal of Economic Development, Environment and People, 2013)
The purpose of multicriteria decision models is to help decision maker to evaluate each alternative and to rank them in descending order of performance. This study analyses the concept of Multiple Attribute Decision Making for using in local government area. The aim of this paper is to analyse the concept of Multiple Attribute Decision Making for selecting the most efficient municipality in selected district in the Slovak Republic. Achieving this purpose, TOPSIS technique (in two variants) is used as decision making tools.